Spectrophotometric Determination of Buflomedil Hydrochloride with Oxidation of Potassium Permanganate - Liu, Ying-Hong; Peng, Fu-You; Ma, Wei-Xing (Asian Journal of Chemistry, 2011)
A new spectrophotometric method was developed for the determination of buflomedil hydrochloride. The method was based on the oxidation of the drug with potassium permanganate in alkaline medium. Potassium permanganate reacted to buflomedil hydrochloride with the absorbance increasing at 430 and 610 nm and decreasing at 518 nm obviously in the presence of sodium hydroxide. The variation values of absorbance were linear to the concentration of buflomedil hydrochloride within the range of 1-22 μg mL-1. The apparent molar absorption coefficients were 1.7 × 104, 0.7 × 104 and 1.2 × 104 L mol-1 cm-1 at 430, 518 and 610 nm, respectively. By superposing the absorbance at the three wavelengths, the apparent molar absorption coefficients increased to 3.9 × 104 L mol-1 cm-1. The proposed method was applied to the determination of buflomedil hydrochloride in pharmaceutical dosage forms with the recovery of 98.2-102.5 %.